Proteomics and Penicillium chrysogenum: Unveiling the secrets behind penicillin production - Barreiro, Carlos; García-Estrada, Carlos (Journal of proteomics, 2019)
Discovery, industrial production and clinical applications of penicillin, together with scientific findings on penicillin biosynthesis and its complex regulation, are model milestones of the historical evolution of the most recognized ‘magic bullet’ against microbial infections available in the worldwide market. Thousands of tons of penicillin produced nowadays are the result of a huge number of technical, industrial and scientific tackled and solved challenges. This combination of, sometimes unsuspected, findings has given Proteomics the chance to support the understanding of the physiology of the high-producing fungal strains and the development of enhanced mutants by means of inverse engineering. Thus, this review, which is part of the special issue entitled “A Tribute to J. Proteomics on its 10th Anniversary”, describes how Proteomics has contributed to characterize different aspects related to penicillin production in Penicillium chrosogenum. It covers from global proteome characterizations (intracellular, extracellular and microbodies) to proteome-wide comparative analyses between different penicillin-producing mutant strains and conditions, paying special attention to the methodologies used, as well as to the most important outcomes. As a result, a guide of Proteomics approaches applied to the characterization of penicillin production by P. chrysogenum is detailed in the birthday of the Fleming's most relevant finding. Although the discovery of penicillin is celebrating the 90th birthday and its clinical application is worldwide recognized, in fact, semisynthetic penicillins are still one of the most prescribed antibiotics, only the arrival of the post-genomic era during the first decade of the 21st century, and more precisely the Proteomics approaches, have contributed to unveil the industrial secrets behind penicillin production. This review provides relevant information, based on proteomics studies, about the molecular mechanisms responsible for increased penicillin titres, and therefore, may represent a clear model of inverse engineering in microorganisms. [Display omitted] •Current state of penicillin is a proper combination of motley technical factors.•Proteomics approaches to penicillin-producing strains just started ten years ago.•Industrial evolution of mutant strains has been characterized using Proteomics•Proteome analyses pave the way for reverse engineering.•Intra-, extra-cellular and microbody proteomes were analysed in P. chrysogenum.